2021
DOI: 10.3390/ijerph18063122
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Spatial Distribution of Potentially Toxic Elements in Surface Soil of a Peak-Cluster Depression, Babao Town, Yunnan Province, China

Abstract: Potentially toxic elements (PTEs) in Chinese agricultural soils, including those in some heritage protection zones, are serious and threaten food safety. Many scientists think that these PTEs may come from parent rock. Hence, at a karst rice-growing agricultural heritage area, Babao town, Guangnan County, Yunnan Province, China, the concentrations of eight PTEs (As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn) were determined in 148 surface soil, 25 rock, and 52 rice grain samples. A principal component analysis (PCA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Thus, the study of heavy metal pollution in soils is the need of the hour. Many studies have been conducted to explore the spatial distribution of heavy metal pollution in roadside soils [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the study of heavy metal pollution in soils is the need of the hour. Many studies have been conducted to explore the spatial distribution of heavy metal pollution in roadside soils [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of parameters, the huge data and the variability of data, can designate the level of pollution, but make it difficult to compare the pollution levels of various sites. To overcome this problem, a broad ranging approach has been applied by various researchers to assess the soil pollution, which includes the usage of various indices, such as the heavy metal pollution index (HPI), geoaccumulation index (Igeo), enrichment factor (EF), contamination factor (CF) and ecological risk index (RI) [21,24,[34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of PTE in lime soil is high, but in a relatively stable state under the background of calcium-rich geochemistry [35]. Cd in the karst areas of southwest China exceeded the standard rate of 95.83% in the previous study, but the water-soluble and exchangeable Cd concentration only accounted for 0.14% and 1.68%, respectively [36], and the Cd concentration in food crops does not exceed the edible safety standards [37]. However, 95% of rice grains harvested from limestone soil in Guangxi had a Cd concentration over the maximum permissible concentration [38].…”
Section: Correlation Analysis For Source Identification Of Pte In Soilmentioning
confidence: 89%
“…Natural phenomena and anthropogenic activities are the two major sources that determine the concentrations of PTEs in soils [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Natural phenomena are described as the components generated from parent material, whereas anthropogenic sources primarily originate from acute human activities [ 17 , 18 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural phenomena and anthropogenic activities are the two major sources that determine the concentrations of PTEs in soils [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Natural phenomena are described as the components generated from parent material, whereas anthropogenic sources primarily originate from acute human activities [ 17 , 18 , 25 , 26 ]. Many authors have revealed that natural sources of some PTEs (such as Pb, Cd, and Hg) have been surpassed by anthropogenic deposits into soils due to pedogenesis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%